2009
DOI: 10.3164/jcbn.08-244
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Corrected Rapid Turnover Protein Increment Index (CRII) for Early Detection of Improvement of Nutrition Status in Patients with Malnutrition

Abstract: Serum prealbumin level is useful for assessment of changes in nutritional status but it is markedly affected by the inflammation. In this study, we examined the efficacy of the corrected rapid turnover protein increment index (CRII) for prealbumin, which is calculated as [prealbumin level/C-reactive protein (CRP) level on the assessment day]/[prealbumin level/CRP level on the day of starting nutritional care], for prediction of improvement of nutritional status in patients with malnutrition. The subjects were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The purpose of this study was to determine which biological parameter(s) could best monitor efficacy of renutrition, itself considered successful when a patient gained at least 5% of weight. The biological marker most frequently used for this purpose is serum transthyretin concentration, which reacts quickly to any change in nutritional status and nitrogen accretion, 8,26 although its specificity has long been a subject of debate 4–7 . In reality, serum transthyretin and serum albumin are influenced by haemoconcentration and inflammation 4–6 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The purpose of this study was to determine which biological parameter(s) could best monitor efficacy of renutrition, itself considered successful when a patient gained at least 5% of weight. The biological marker most frequently used for this purpose is serum transthyretin concentration, which reacts quickly to any change in nutritional status and nitrogen accretion, 8,26 although its specificity has long been a subject of debate 4–7 . In reality, serum transthyretin and serum albumin are influenced by haemoconcentration and inflammation 4–6 .…”
Section: Discussionmentioning
confidence: 99%
“…The biological marker most frequently used for this purpose is serum transthyretin concentration, which reacts quickly to any change in nutritional status and nitrogen accretion, 8,26 although its specificity has long been a subject of debate. [4][5][6][7] In reality, serum transthyretin and serum albumin are influenced by haemoconcentration and inflammation. [4][5][6] This is well illustrated in our study which, despite a relatively small number of patients, found that changes in transthyretin concentrations were highly negatively correlated with changes in CRP levels and highly positively correlated with changes in albumin concentrations, but were not associated with successful renutrition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations